1977
DOI: 10.1002/jsfa.2740280602
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oven and toluene dry matter in grass silage

Abstract: Dry matter (DM) contents of 205 silages were determined by toluene distillation and oven drying at 100°C. The toluene distillation method gave values up to 11 % higher than the oven drying method, the largest differences occurring with silages of high volatile fatty acid concentration, low lactic acid concentration and high ammonia nitrogen content expressed as a percentage of total nitrogen. Highly significant (P< 0.01) correlations were shown between toluene dry matter and oven dry matter for various ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…Silage ammonia N was higher in timothy than in ryegrasses in both years. However, ammonia N was less than lOVa of total N in all cases which indicated that proteolytic activity was at a minimum in the silages (Haigh and Hopkins 1977).…”
mentioning
confidence: 78%
“…Silage ammonia N was higher in timothy than in ryegrasses in both years. However, ammonia N was less than lOVa of total N in all cases which indicated that proteolytic activity was at a minimum in the silages (Haigh and Hopkins 1977).…”
mentioning
confidence: 78%
“…Both NDF and ADF were expressed without residual ash. Moisture content of the silages was determined through distillation with toluene (HAIGH & HOPKINS, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…Both NDF and ADF are expressed without residual ash. Moisture content of the silages was determined through distillation with toluene (Haigh & Hopkins, 1977).In vitro gas production (GP, mL gas g -1 DM) and in vitro dry matter disappeared (DMd) were determined following the technique described by Theodorou et al (1994). A DM sample of 800 mg was placed in a 125 mL flask with 90 mL of incubation solution (Menke & Steingass, 1988).…”
mentioning
confidence: 99%